PUSAT PENAMPUNGAN HEWAN DI KOTA PONTIANAK - Meyliany, Meyliany; Alhamdani, Muhammad Ridha; Andi, Uray Fery (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
The surging number of pet ownerships has mirrored the trajectory of the growth of human population, ultimately contributing to the commercialization of pets. Practices carried by breeders or pet shops often neglect animal welfare. The lack of public education and awareness about pet ownership